Current Status of and Challenges in Regional Policies in Japan: Współczesny status japońskiej polityki regionalnej i stojące przed nią wyzwania - Ichishima, Munenori (Investigationes Linguisticae, 2020)
This study aims to explain current regional policies in Japan and to explore challenges in relation to the same. Specifically, I will focus on regional revitalisation policies implemented by the Abe cabinet since 2014 and examine whether grants for regional revitalisation policies are distributed in a way that political scientists have disputed for a long time. From the perspective of public policy analyses in political science, I will conduct statistical analyses by using aggregated data of local municipalities in Japan. Thus, I will clarify the current status of and challenges related to regional policies in Japan.